10-YEAR-OLD PAKISTANI BOY WITH MULTIPLE MALIGNANCIES: LOSS OF PMS2-CONSTITUTIONAL MISMATCH REPAIR DEFICIENCY - Rehman, Palwasha; wali, Rabia Muhammad (Journal of Ayub Medical College Abbottabad, 2022)
Constitutional Mismatch repair deficiency (CMMRD) is a cancer predisposition syndrome. Four main common malignancies seen are, hematological, brain tumours, colorectal cancers, and intestinal polyps. We are reporting a 10-year-old boy with CMMRD; diagnosed with hematological malignancies, followed by low grade glioma in thalamus. There was loss of PMS2, whereas immunostaining was retained for MLH1, MSH2 and MSH6. Early diagnosis of CMMRD is crucial especially in countries like Pakistan, where consanguineous marriages are common. Increasing awareness among the physicians will help in early diagnosis, surveillance and in providing appropriate genetic counselling to the family.